FOREIGN EXPERIENCE IN THE FIELD OF LIBERALIZATION OF THE EDUCATIONAL PROCESS AND THE WAYS OF USING IT (Academicia Globe: Inderscience Research, 2021)
Education is one of the most important issues in all period. Today, various measures are being carried out further improvement this process in our country. This article discusses the liberalization of the educational process by exploring ways to use foreign experience.